About the development of spatial methods of calculating spans of highway bridges - Kozhushko, V. P. (Science and Transport Progress, 2008)
The problem of methods of spatial computation of spans of different structures has been considered. The possibility of application of simplified computation methods allowing to take into account both resilient and non-linear deformations as well as to estimate other factors affecting the stressed-and-strained state of a system without accuracy loss for results obtained has been presented.